A Rare Case of Osteomyelitis Caused by Scedosporium Apiospermum in the Right Foot of an Immunocompetent Patient - Yu Z; Su S; Xiong X; Huang W; Tong T; Peng Z (Infection and Drug Resistance, 2025)
Zejun Yu, Songchuan Su, Xiaotian Xiong, Wenping Huang, Ting Tong, Zhenggang Peng Foot & Ankle Surgery, Chongqing Orthopedic Hospital of Traditional Chinese Medicine, Chongqing, People’s Republic of ChinaCorrespondence: Ting Tong, Email 17823540061@163.com Zhenggang Peng, Email 252800162@qq.comBackground: Fungal osteomyelitis is rare in clinical practice, and osteomyelitis caused by Scedosporium apiospermum is even rarer, which is easy to misdiagnose, and it is resistant to many antifungal drugs, which makes it tricky to treat. Early diagnosis and accurate treatment are essential.Case Presentation: A 38-year-old healthy male has been experiencing recurrent pain in his right foot, accompanied by skin ulcers and exudate, for the past five years. He has been diagnosed with bacterial osteomyelitis at other hospitals as well as at our hospital. In the first stage, osteomyelitis lesion removal + vancomycin bone cement tamponade was used, and the infected bone tissue was taken for microbial culture and morphological observation, and identified as Scedosporium apiospermum. The patient was cured after postoperative treatment with voriconazole. No further signs of infection or Scedosporium apiospermum were detected during the second stage of bone reconstruction surgery, and the incision healed with grade A healing and no further signs of osteomyelitis, such as bone destruction, were detected after bone reconstruction surgery.Conclusion: : This is a rare case of Scedosporium apiospermum osteomyelitis of the right foot, which was successively misdiagnosed and finally cured by surgery and antifungal treatment with voriconazole. Given that Scedosporium apiospermum is extremely rare and resistant to antifungal drugs, this case highlights the importance of microbiologic culture and pathologic examination, surgical debridement, and precise antifungal treatment.Keywords: foot, scedosporium apiospermum, osteomyelitis, surgical debridement, antifungal treatment